Re- styling civilizations: Understanding changing repertoire of elegance in male dress fashions - Karunaratne, P.V.M. (Faculty of Graduate Studies, University of Kelaniya, 2015)
This paper explores the necessity to take further analytical reading of the critical issues of hybrid male dress by using the knowledge on cultural authentication. Furthermore, paper this examines how the elements of dress from one source culture and the receiving culture merged. The study revealed how the process of cultural authentication incorporated into new settings and how the elements of dresses transformed. At a one moment fashions of dresses in society changed as Western and then appeared as non-Western. Many scholars addressed this issue of arbitrariness of the Western and non- Western categories of fashion. This revealed us the human societies are subjected to be continuously receiving from each other stimuli incorporating social, cultural, economic and political developments also internal and external influences that affect dress. This process resulted in generating new hybrid clothing styles. Scholars also argued Western fashions of dress are one of multiple global traditions that co-exist with long established cultural traditions. It is seen that Sri Lankan fashion markedly affects contemporary fashions in Western Europe. A qualitative research method was adopted for the research. Sequence of observational studies carried out with temple paintings, wood carvings, sculptures, cloth paintings and ivory carvings. The literary data were gathered from many original documents. Validations of data were much concerned. Sri Lanka was first exposed to Western during early phase of the 16th century when the Portuguese conquered the island. During this period the male dress fashion created a social distinction within Sri Lanka. Inspiration and hybridization were part of the process by which Western dress fashions and etiquette were adopted. Numbers of dresses were worn by the King and elite male show changing repertoire of elegant hybrid fashion etiquettes.
Keywords: Cultural Authentication; Tradition; Culture; Hybrid clothing styles; Fashion